Violence as a resource. On modes of use, conditions and chains (Delito y Sociedad, 2021)
Our challenge is to analyze how violence is used, to understand its logic of action and its conditioning. As a result of the comparison of two ethnographic investigations we propose a reflection on the violence that illuminates three nodal areas for the discussion on this concept. First, we will interpret violence as a resource and analyze its use criteria. Second, we will study the social conditions that define the use of this resource. Finally, we will analyze how the conditions of use are linked to social inequalities
Keywords: Violence; Legitimacy; Conditions